Effect of Supplementation of Palm Kernel Meal with and without Enzyme on the Performance of Japanese Quail (Coturnix Coturnix Japonica) - Ali, M. Mahammad; Nath, D. Narendra; Kumari, K. Nagaraja; Rao, B. Eswara (International Journal of Livestock Research, 2019)
A study was conducted to assess the influence of palm kernel meal (PKM) inclusion with and without enzyme supplementation on growth performance and production cost of Japanese quail. A total of 180 day-old Japanese quail chicks were individually weighed and randomly allotted into six treatment groups with three replicates containing ten birds each. Six experimental diets were prepared as 0 (control), 15 and 20% incorporation of PKM respectively with and without enzyme addition. Feed intake, body weight, body weight gain, feed conversion ratio (FCR) production economics were studied and analysed in a 3×2 factorial method. Body weight gain, feed intake were not influenced by either PKM or enzyme supplementation. Whereas better (p<0.01) FCR was observed in diets with 15% PKM with addition of enzyme. Cost of production per Kg live gain was low (p<0.01) in PKM included groups and lowest production cost was observed (p>0.01) at 15% PKM with enzyme supplementation. It can be concluded that PKM supplemented with enzymes can be incorporated up to 15% in quail diets without any adverse effects on performance.